PENGARUH MOBILISASI DINI TERHADAP PROSES PENYEMBUHAN LUKA PADA PASIEN POST OPERASI SECTIO CAESAREA DI RSUD ANDI DJEMMA MASAMBA - Wanto Sinaga; Muhammad Useng; Fendy Yesayas (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Wound healing is an important physiological process to maintain skin integrity as a mechanical barrier after trauma. In general, it can be divided into hemostatic, inflammatory, proliferative, and remodeling phases. Early mobilization is carried out to reduce the risk of postoperative complications, accelerate the recovery of functional walking capacity, have a positive impact on some of the outcomes reported by patients and reduce the length of hospital stay, thereby reducing treatment costs. This study aims to determine the effect of early mobilization on the wound healing process in postoperative Sectio Caesarea patients at Andi Djemma Masamba Hospital.This study uses a pre-experimental type of research with a one shot case study approach (one group pretest and post test design). The population in this study were all patients with sectio caesarea surgery in July as many as 72 people. The number of samples in this study was 42 people. This study uses observation sheets and SOPs for early mobilization. The data analysis test used was the Wilcoxon test because the data were not normally distributed.The results of the analysis test found that there was an effect of early mobilization on the wound healing process in postoperative Sectio Caesarea patients at Andi Djemma Masamba Hospital with a p value of 0.000 which was smaller than the value of 0.05.Suggest for hospital management to make early mobilization a mandatory intervention that must be carried out by post Sectio Caesarea patients..